2021
DOI: 10.1007/s10924-021-02335-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elucidation and Immunostimulatory Activities of Quinoa Non-starch Polysaccharide Before and After Deproteinization

Abstract: Non-starch polysaccharides derived from natural resources play a significant role in the field of food science and human health due to their extensive distribution in nature and less toxicity. In this order, the immunostimulatory activity of a non-starch polysaccharide (CQNP) from Chenopodium quinoa was examined before and after deproteination in murine macrophage RAW 264.7 cells. The chemical composition of CQNP and deproteinated-CQNP (D-CQNP) were spectrometrically analysed that revealed the presence of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Although papain has a hydrolytic effect, these proteins were also dissolved in the extraction solution during the reaction, so although treated with protein removal, the polysaccharides extracted by ultrasound-assisted enzymatic method had the most protein impurities in comparison. Studies have shown a strong correlation between polysaccharide activity and its glyoxylate content, so it is interesting to use extraction methods that increase the glyoxylate content of polysaccharides [24] , [25] .…”
Section: Resultsmentioning
confidence: 99%
“…Although papain has a hydrolytic effect, these proteins were also dissolved in the extraction solution during the reaction, so although treated with protein removal, the polysaccharides extracted by ultrasound-assisted enzymatic method had the most protein impurities in comparison. Studies have shown a strong correlation between polysaccharide activity and its glyoxylate content, so it is interesting to use extraction methods that increase the glyoxylate content of polysaccharides [24] , [25] .…”
Section: Resultsmentioning
confidence: 99%
“…The influence of the protein part on the biological activity of the whole protein–PS conjugate/complex is still not a regular subject of study during the evaluation of immunomodulatory activity (including molecular mechanisms of action) of mushroom PSs. It has been demonstrated that a PS–protein complex CQNP from Chenopodium quinoa induces lower iNOS expression and NO production in RAW264.7 cells than the deproteinized PS sample D-CQNP [ 76 ]. The activation of NF- κ B and MAPK signaling pathways by D-CQNP is similar to that of LPS.…”
Section: Discussionmentioning
confidence: 99%
“…When we investigated the effect of removing protein, the phenol–sulfuric acid method and the Folin–phenol method were used to determine the content of polysaccharides and protein before and after protein removal (Cao et al, 2022 ). The polysaccharide retention rate, protein clearance rate, and comprehensive score were used as indicators to evaluate the effect of protein removal.…”
Section: Methodsmentioning
confidence: 99%
“…Recent pharmacological studies have shown that Lonicera japonica polysaccharides have a broad spectrum of biological activity, including anti‐allergic, antipancreatic cancer, hypoglycemic, hypolipidemic, and neuroprotective effects (Lin et al, 2016 ; Liu, Huang, & Hu, 2018 ; Tian et al, 2012 ; Wang et al, 2017 ; Zhao et al, 2018 ). However, we found that polysaccharides extracted by water often contain more protein, which affects further study of their chemical properties and pharmacological activities (Cao et al, 2022 ; Younes & Rinaudo, 2015 ). To optimize the best approach and the best condition of deproteinization, five methods were investigated, including the enzymatic method, Sevage method, enzymatic–Sevage method, trichloroacetic acid (TCA) method, and TCA–n‐butanol method.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation